ANALISIS KOMPETENSI PROFESIONAL GURU EKONOMI DI SMA NEGERI KECAMATAN ILIR BARAT I PALEMBANG - Rusmin AR; Deskoni Deskoni; Ikbal Barlian; Edutivia Mardetini (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
This research is aimed to describe the professional competences of economic teachers at SMA Negeri Kecamatan Ilir Barat I Palembang. It is a qualitative descriptive research. The subjects of this research were all of economic teachers forwhom had educational sertificate at SMA Negeri Kecamatan Ilir Barat I Palembang. The data collection was done through observation,interview, and documentation. In analyzing the data, the researcher used descriptive data analysis through data reduction, data classification, data interpretation, data display, and inference. Validity test was conducted through source triangulation. The result shows that the highest indicator was learning planning shows the results of 91,66%, itꞌs indicated a highest criteria. Understanding of professional development shows the results of 82,23% itꞌs indicated a highest criteria, so the average total of both indicator show the results of 87,02% itꞌs indicated a highest criteria.